POLA HIJRAH ZAMAN NOW PERSPEKTIF ‘UZLAH: Indonesia - Muhammad Zamroni (Universitas Islam Negeri Mataram, 2021)
The word hijrah is currently experiencing an expansion of meaning. Initially, hijrah meant moving from one place to another in search of protection. Now hijrah is interpreted as a condition in which a person intends and is committed to being better. Hijrah is the realization of repentance that is done first and has implications for positive attitudes in society. The implementation of this hijrah is carried out first to continue implementing 'uzlah. As for 'uzlah is an action taken by someone who tries to isolate himself from the crowd to get closer to Allah swt. namely, focusing on taqarrub to Allah swt. Seeing the concept of hijrah, there is a similarity in meaning to the concept of 'uzlah in Sufism. Therefore, here the author tries to compare the two. If we compare today's hijrah with 'uzlah' then we will find a common ground that today's hijrah is a person's starting point to do 'uzlah to Allah swt. If someone can carry out the hijrah correctly, implement the values ??of the hijrah that he is living, then over time that person will definitely try to make 'uzlah' to Allah swt. Because when there is a person's intention and commitment to emigrate, it will not be perfect if his worldly affairs are still above his ukhrawi affairs. When someone has emigrated with the true meaning of hijrah, then that will lead him to the act of 'uzlah to Allah swt. The perfection of 'uzlah will be felt when someone who has migrated has implemented the concepts of takhalli, tahalli, and tajalli well.